RELATIONSHIP BETWEEN UTILIZATION OF COLLECTION DEVELOPMENT PROCESSES AND BUILDING LIBRARY COLLECTION - Abdulrahman Yusuf; Sanda Grema (Edulib, 2020)
This study determined the relationship between utilization of Collection Development Process and Building Library Collections in Federal University Libraries in North-Eastern Nigeria. The study was guided by Six objectives which were to determine the extent of utilization of collection development process and the relationship between utilization of community analysis, collection development policies, selection criteria, acquisition procedure, weeding as well as resource evaluation procedures and building library collection in libraries under study. To achieve these objectives six research questions developed and six null hypotheses were formulated and tested. It was hypothesized that, there is no significant relationship between the utilization of community analysis, selection policy, selection criteria, acquisition procedure, weeding procedure and resource evaluation procedure and Building Library collection in the libraries under study. The study was a correlational study and used correlational research design. The population for the study was made up of fifteen staff of the selected federal university libraries in the North-East Zone, Nigeria, working in the Collection Development Divisions. All the population were used for the study. The research instrument for this study was a self-designed questionnaire that was complemented with a checklist. A 4-point likert type scale questionnaire was used for data collection. Data was analyzed using descriptive statistics of frequency counts, percentage scores, and Pearson product Moment Correlation coefficient (PPMC) was used to test the hypotheses at 0.05 level of significance. The hypotheses tested revealed that, there was a significant relationship between utilization of community analysis, acquisition procedure and Building library collection in libraries under study. On the basis of the findings, conclusion drawn, recommendations were made for the improvement of utilization of collection development process in building library collections. The study recommends that the university libraries under study should increase partnership with the faculty to explore especially in the determination of materials to acquire; faculty members should be in a position to make valid judgment (selection) on relevance of tests to be included in the collection, hence their increased involvement in material selection will add to the richness of the library collection; a formalized comprehensive collection development policy should be developed and operated in the libraries studied, and the document should be reviewed periodically for up-to-datedness; weeding should be a periodic exercise in the libraries studied, so as to rid the shelves of irrelevant or unusable materials and increase access to usable ones; the libraries studied should create a Collection Department with a mandate to coordinate all collection development activities; of selection, acquisition, stock evaluation and weeding; collection development librarians should be trained and retrained in the process of building library collection in order to have an effective and efficient library collections.